Identification of microRNAs Actively Involved in Fatty Acid Biosynthesis in Developing Brassica napus Seeds Using High-Throughput Sequencing - Wang, Jia; Jian, Hongju; Wang, Tengyue; Wei, Lijuan; Li, Jiana; Li, Chao; Liu, Liezhao (Frontiers in Plant Science, 2016)
Seed development has a critical role during the spermatophyte life cycle. In Brassica napus, a major oil crop, fatty acids are synthesized and stored in specific tissues during embryogenesis, and understanding the molecular mechanism underlying fatty acid biosynthesis during seed development is an important research goal. In this study, we constructed three small RNA libraries from early seeds at 14, 21 and 28 days after flowering (DAF) and used high-throughput sequencing to examine microRNA (miRNA) expression. A total of 85 known miRNAs from 30 families and 1,160 novel miRNAs were identified, of which 24, including 5 known and 19 novel miRNAs, were found to be involved in fatty acid biosynthesis. bna-miR156b, bna-miR156c, bna-miR156g, novel_mir_1706, novel_mir_1407, novel_mir_173, and novel_mir_104 were significantly down-regulated at 21 DAF and 28 DAF, whereas bna-miR159, novel_mir_1081, novel_mir_19 and novel_mir_555 were significantly up-regulated. In addition, we found that some miRNAs regulate functional genes that are directly involved in fatty acid biosynthesis and that other miRNAs regulate the process of fatty acid biosynthesis by acting on a large number of transcription factors. The miRNAs and their corresponding predicted targets were partially validated by quantitative RT-PCR. Our data suggest that diverse and complex miRNAs are involved in the seed development process and that miRNAs play important roles in fatty acid biosynthesis during seed development.